12 UMP lecturers listed as 2 world s best scientists - Mimi Rabita, Abdul Wahit (2021)
KUANTAN, 28 October 2021 - Twelve Universiti Malaysia Pahang (UMP) lecturers are listed among the two per cent of the best scientists in the world in various fields and disciplines.